2022
DOI: 10.1177/17588359221110176
|View full text |Cite
|
Sign up to set email alerts
|

Tumor vessel normalization and immunotherapy in gastric cancer

Abstract: Gastric cancer (GC) is a common malignant tumor, and patients with GC have a low survival rate due to limited effective treatment methods. Angiogenesis and immune evasion are two key processes in GC progression, and they act synergistically to promote tumor progression. Tumor vascular normalization has been shown to improve the efficacy of cancer immunotherapy, which in turn may be improved through enhanced immune stimulation. Therefore, it may be interesting to identify synergies between immunomodulatory agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 176 publications
0
2
0
Order By: Relevance
“…The crosstalk between angiogenesis and immunosuppression mechanisms within the tumor microenvironment and the therapeutic potential for the combination of antiangiogenic therapy and immunotherapy are now well-recognized ( 47 49 ). Based on the finding of this study, multitarget antiangiogenic combination therapy opens the avenue for the addition of an immunotherapy agent to achieve the best antitumor response in GAC.…”
Section: Discussionmentioning
confidence: 99%
“…The crosstalk between angiogenesis and immunosuppression mechanisms within the tumor microenvironment and the therapeutic potential for the combination of antiangiogenic therapy and immunotherapy are now well-recognized ( 47 49 ). Based on the finding of this study, multitarget antiangiogenic combination therapy opens the avenue for the addition of an immunotherapy agent to achieve the best antitumor response in GAC.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that rhMIF restored ART‐induced downregulation of VEGF and IL‐8 expression, tumour inhibition, vascular normalisation, and the efficiency of cisplatin transport, implicating the crucial roles of MIF in ART‐mediated antitumor effects. Moreover, tumour vascular normalisation and immune reprogramming have a synergistic effect and can enter a mutually reinforcing virtuous circle by improving the tumour microenvironment (Luo et al, 2022; Viallard & Larrivée, 2017; Yu et al, 2022). Our study demonstrated that ART could promote tumour vascular normalisation through MIF and also affect the expression of MIF, IL‐8 and VEGF, which are associated with immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Although these possible interactions were not validated at the protein level, these findings suggest an involvement of CCL2 + ECs in establishing an immunosuppressive TME in deep layers of gastric cancer 84 . Although current AATs did not show a beneficial effect in gastric cancer, continuous efforts have shown encouraging results of combining AATs with immunotherapies in this cancer type 88 .…”
Section: [H3] Stomachmentioning
confidence: 97%